Data Transactions in China: Legislation, Promotion, and Regulation - Yang, Li; Hu, Jieren (International Journal of Digital Law and Governance, 2024)
The difficulty of deepening the promotion of “factor-level” data circulation and utilization lies in the feasibility of the legislation of data transaction. This involves meta-issues such as the definition of data ownership, the positioning of data assets, and privacy protection systems. From the perspective of inclination, i.e., focusing on promotion while giving consideration to regulation, the legislation of data transaction in China is established on the theoretical basis of an “incomplete contract”. Such perspective identifies different areas that can be the subject of regulation, ranging from data rights, behavior control to the separation of personal data and information. On this basis, the driving mode of the legislation of data circulation and utilization is not the simple and direct data transaction with market-oriented mechanism, but the exploration of data licensing under government authorized operation beforehand in China. Such approaches should be considered during the licensing of public data, and the government’s right to obtain necessary compensations for the costs of data processing should be reserved. What’s more, legislative clauses of data security are essential in transactions, but compliance and conditional liability exemptions can be adopted to safeguard the realization of the goals of data transaction to a great extent.